THU0593 Validity of The Bristol RA Fatigue Multi-Dimensional Questionnaire (BRAF-MDQ) and Rheumatoid Arthritis Impact of Disease (RAID) Scale across 6 European Countries. (15th July 2016) - Hewlett, S.; Nicklin, J.; Bode, C.; Cramp, F.; Carmona, L.; Davis, B.; Dures, E.; Engelbrecht, M.; Fransen, J.; Greenwood, R.; Hagel, S.; Kirwan, J.; et al.
Abstract : Background: The BRAF-MDQ 1, 2 and RAID 3 are patient-reported outcome measures derived from the patient perspective. The 20 item BRAF-MDQ has 4 factors (physical, cognitive, emotional fatigue, living with fatigue) and the 7 item RAID is uni-dimensional. The BRAF-MDQ properties have not been tested outside the UK, nor the validity of the new Swedish RAID examined. Objectives: To test the structure, construct and criterion validity of the BRAF-MDQ and the RAID in 6 EU countries. Methods: Survey of RA clinic patients in clinics in France, Germany, Netherlands, Spain, Sweden and UK (F, G, N, Sp, Sw, UK), using BRAF-MDQ, RAID and SF-36. Factor structure examined by Confirmatory Factor Analysis and internal consistency by Cronbach's Alpha. Criterion validity for the BRAF-MDQ evaluated by internal Spearman's correlations, and for BRAF-MDQ and RAID fatigue item by correlation with each other and SF-36 Vitality subscale. Construct validity of BRAF-MDQ and RAID evaluated by Spearman's Correlation with each other, HAQ, and SF-36 domains. Analysis conducted overall and by individual country and for BRAF-MDQ by total and subscales. Results: 1276 patients participated: F 206, G 216, N 317, Sp 157, Sw 170, UK 210. Disease duration <5 yrs for 25%, 76% female, median HAQ 1.0 (IQR 0.375–1.5). Mean total BRAF-MDQ was 26/70 (SD 26) with subscales physical fatigue 11.38/22 (SD 5.77), living with fatigue 6.46/21 (SD 5.4), cognitive 4.28/15 (SD 8.7) and emotional fatigue 3.41/12 (SD 3.22). Mean RAID was 4.15/10 (SD 2.31). Confirmatory factor analysis: BRAF-MDQ original UK 4 factor structure was confirmed in each country, demonstrating one factor for each set of variables, with high factor loadings (0.71–0.96). Bootstrapping (4 sets of analyses on 20 random samples of 50% of patients/country), found the structure held true in at least 19/20 sets per country. RAID single factor structure was confirmed in all countries (0.75–0.95). Internal consistency ranged from 0.75–0.96 for the BRAF-MDQ (total and subscales) and the RAID ranged from 0.93–0.96 (overall and by country). Criterion validity overall and by country: The BRAF-MDQ correlated internally and with the SF-36 Vitality and RAID fatigue items (0.6–0.93). Construct validity: BRAF-MDQ and RAID correlatied with each other, the HAQ, and remaining 8 SF36 domains (0.46–0.86). Conclusions: The BRAF-MDQ and RAID demonstrate strong, consistent factor structure and internal consistency, with moderate-good criterion and construct validity across 6 EU countries, reflecting their robust methods of development. This indicates no specific country scoring is necessary, and strengthens the case for measuring both fatigue and impact in multi-country studies. References: Nicklin et al, Arth Care Res 2010:62:1552–8. Nicklin et al, Arth Care Res 2010:62:1559–6. Gossec et al, Ann Rheum Dis 2009;68:1680–5 Acknowledgement: EULAR project grant EP1009 Disclosure of Interest: None declared